Cómo evitar fracasos en prótesis dental parcial removible (2008)
ABSTRACT: A removable partial prosthesis is a therapeutical modality used to restore partial edentulous ridges in which a fixed partial prosthesis is not indicated. Removable partial prosthesis although is an excellent way to restore lost teeth could become a serious threat for the remmant teeth due to possible lever effect exerted on the structure when it is not adequately planned. Preservation of remmant teeth and optimization of function of the masticatory system are the main objectives of removable partial prosthesis. The purpose of this review is to identify the causes of failure of removable partial prosthodontics keeping in mind the benefits provided to the patient when there are no other alternatives.